Healthy Snacks for Children - Jennifer Hillan (EDIS, 2006)
FCS8823, a 2-page fact sheet adapted by Jennifer Hillan from a Center for Science in the Public Interest document, is full of ideas and suggestions for nutritious, easy-to-prepare snacks for children. Published by the UF Department of Family, Youth and Community Sciences, December 2006.